1993
DOI: 10.1039/c39930000197
|View full text |Cite
|
Sign up to set email alerts
|

Metathesis vs. Polymerization of terminal acetylenes over [W(CBut)(OBut)3]

Abstract: Terminal acetylenes RC-CH are transformed catalytically into metathesis products RC=CR and C2H2 on the carbyne complex [W(CBU~)(OSU~)~], a process which is rapidlyfollowed by a polymerization of the alkyne; in the case of sterically hindered ButC-CH, a stoichiometric reaction is observed, by which a dinuclear compound p-C2H2[W(OBut)& 1 and the deprotiotungstenacyclobutadiene [ W C 3 ( B ~f ) 2 ( 0 B ~t ) 2 ] 2 are formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
42
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 9 publications
(5 reference statements)
2
42
0
4
Order By: Relevance
“…[13] The length of the W W triple bond, 2.430 (8) , is comparable to that in similar complexes in the literature. [14] The ether function of one of the ligands coordinates the other tungsten atom with a W À O length of 2.257(3) , vs. 1.957(3) , 1.897(3) , and 1.920(3) for the three W À O bonds to non-bridging ligands.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…[13] The length of the W W triple bond, 2.430 (8) , is comparable to that in similar complexes in the literature. [14] The ether function of one of the ligands coordinates the other tungsten atom with a W À O length of 2.257(3) , vs. 1.957(3) , 1.897(3) , and 1.920(3) for the three W À O bonds to non-bridging ligands.…”
supporting
confidence: 56%
“…[7] Using the same catalyst we have demonstrated some promising results on alkyl-monosubstituted alkynes using diethyl ether as solvent. [8] More recent results in our group have shown that the addition of an external ligand such as quinuclidine to complex 1 could improve the selectivity: an 80 % metathesis selectivity was attained using hept-1-yne as substrate. [9] Based on the idea that coordination at the metal centre was responsible for this improvement in selectivity, we decided to look at the synthesis of new catalysts where ligand modification would give rise to variable coordination within the first coordination sphere of the metal by using a hemilabile ligand.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…A general mechanistic scheme related to this chemistry is given below (scheme 10). In 1993 however, attempts at homogeneous metathesis of terminal alkynes haves been successful, on the well defined (tBuO) 3 W CtBu complex [34]. The use of alkyl monosubstituted alkynes rather than aryl ones led to several turnovers in metathesis at room temperature, which were increased at high temperature (80°C) and upon using diethyl ether as solvent.…”
Section: Metathesis Of Monosubstituted Alkynesmentioning
confidence: 99%
“…These deprotonated metallacycles are highly active catalysts for terminal alkynes polymerization as they are prone to be transformed into metallacarbenes (scheme 10) [34]. Scheme 10: Polymerization of phenylacetylene over deprotonated metallacyclobutadiene [34].…”
Section: Metathesis Of Monosubstituted Alkynesmentioning
confidence: 99%